SOSIALISASI PENERAPAN HIDUP SEHAT DAN PENCEGAHAN PENYAKIT AKIBAT HEWAN TERNAK DI DESA KURIPAN TIMUR KECAMATAN KURIPAN - Dita Triana Dewi; Suharti Suharti; Ida Ermiana; Aulia Patra Nirmala; Baiq Sintia Apriliana; Putri Husnul Amalia (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2023)
Clean and Healthy Living Behavior is an attempt to provide a learning experience or create a condition for individuals, families, groups and society. By opening lines of communication, providing information, andconduct education to increase knowledge as well as attitudes and behavior, through leadership approach, atmosphere building, and empowerment public. the maintenance of livestock is carried out by the people in East Kuripan, namely caring for livestock near the homes or residential areas. through such a maintenance system it becomes one of the sources of disease spread which is very wide and easy. Various types of diseases that often arise as a result of animals that can be transmitted to humans, namely, Bovine Spongiform Encephalopathy (BSE) or mad cow foot and mouth disease (FMD), Brucellosis disease is caused by a lack of attention to the health of these livestock. Through the socialization held, it is hoped that it can change the lifestyle of the community, especially in how to raise livestock.